ASAS MAAF HAKIM (RECHTERLIJK PARDON) SEBAGAI UPAYA PENYELESAIAN TINDAK PIDANA RINGAN UNTUK PEMBAHARUAN HUKUM PIDANA NASIONAL - Manafe, Vita Adolfina; Gultom, Elfrida Ratnawati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
A criminal verdict is a judgment rendered by a court against an individual who has committed a crime or crimes, as per the terms of the criminal procedural legislation that is now in effect in Indonesia. Acquittal, acquittal, or resentencing are the three (3) possible verdicts that might be rendered against a person. The criminal procedural legislation stipulates requirements for the types of decisions that can be made based on the findings of the examination, the facts and evidence produced during the trial, and the type of decision that is rendered to the defendant. However, with the passing of Law Number 1 of 2023, the concept of judge's pardon (rechterlijk pardon) is now governed by Indonesian criminal law. If the defendant is proven to have committed a criminal act, the judge can use extraordinary authority to save him. from prosecution.Keywords: Sorry Judge, Light Crime